Effect of bicarbonate on aging and reactivity of nanoscale zerovalent iron (nZVI) toward uranium removal. (June 2018) - Hua, Yilong; Wang, Wei; Huang, Xiaoyue; Gu, Tianhang; Ding, Dexin; Ling, Lan; Zhang, Wei-xian
Abstract: Bicarbonate, ubiquitous in natural and waste waters is an important factor regulating the rate and efficiency of pollutant separation and transformation. For example, it can form complexes with U(VI) in the aqueous phase and at the solid-water interface. In this work, we investigated the effect of bicarbonate on the aging of nanoscale zero-valent (nZVI) in the context of U(VI) reduction and removal from wastewater. For fresh nZVI, over 99% aqueous uranium was separated in less than 10 min, of which 83% was reduced from U(VI) to U(IV). When nZVI was aged in water, its activity for U(VI) sequestration and reduction was significantly reduced. Batch experiments showed that for nZVI aged in the presence of 10 mM bicarbonate, only 20.3% uranium was reduced to U(IV) after 6 h reactions. Characterizations of the iron nanoparticles with spherical aberration corrected scanning transmission electron microscopy (Cs-STEM) suggest that in fresh nZVI, uranium was concentrated at the nanoparticle center; whereas in nZVI aged in bicarbonate, uranium was largely deposited on the outer surface of the nanoparticles. Furthermore, aged nZVI without bicarbonate contained more lepidocrocite (γ-FeOOH) while aged nZVI in the presence of bicarbonate had more magnetite/maghemite (Fe3 O4 /γ-Fe2 O3 ). This could be attributed to the formation of carbonate green rust and pH buffer effect of . Primary mechanisms for U(VI) removal with nZVI include reduction, sorption and/or precipitation. Results demonstrate that bicarbonate alter the aging products of nZVI, and reduces the separation efficiency and reduction capability for uranium removal. Graphical abstract: Image 1 Highlights: Bicarbonate in water has significant impact on the surface chemistry of nZVI. Bicarbonate converts Fe(0) to magnetite and maghemite. Bicarbonate aged nZVI has low activity for uranium separation and reduction.